CTGF Attenuates Tendon-Derived Stem/Progenitor Cell Aging - Yun-feng Rui; Min-hao Chen; Ying-juan Li; Long-fei Xiao; Peng Geng; Pei Wang; Zheng-yuan Xu; Xuan-pu Zhang; Guang-chun Dai (Stem Cells International)
Aged tendon-derived stem/progenitor cells (TSPCs) lead to age-related tendon disorders and impair tendon healing. However, the underlying molecular mechanisms of TSPC aging remain largely unknown. Here, we investigated the role of connective tissue growth factor (CTGF) in TSPC aging. CTGF protein and mRNA levels were markedly decreased in the aged TSPCs. Moreover, recombinant CTGF attenuates TSPC aging and restores the age-associated reduction of self-renewal and differentiation of TSPCs. In addition, cell cycle distribution of aged TSPCs was arrested in the G1/S phase while recombinant CTGF treatment promoted G1/S transition. Recombinant CTGF also rescued decreased levels of cyclin D1 and CDK4 and reduced p27kip1 expression in aged TSPCs. Our results demonstrated that CTGF plays a vital role in TSPC aging and might be a potential target for molecular therapy of age-related tendon disorders.